Perilaku Kontrol yang Dirasakan Perawat dalam Pendokumentasian Asuhan Keperawatan - Silvia Batulingas; Wastu Adi Mulyono; Eni Rahmawati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background : Nursing documentation is an important aspect of nurse profesionalism. Therefore each nurses should write down their activity properly according their role. However, to keep nurse documenting their prefossional behavior have been challanging according to studies. Objective: This study aims to portray how nurses perceived behavior control toward nursing documentation in hospital. Method: an observational study was conducted to investigate perceived behavior control among nurses working in ward setting. A total sampling technique was applied to recruite 47 nurses work in pediatric ward. Univariate analysis was utilized. Results: Most respondents were female, age 37.9 (7.5) years old on average, with undergraduate in nursing education background. Currently nurses were qualified for the first level of clinical nurse’s career path (PK 1), and working as associate nurses. The average score of nurses’ perceived control behavior over nursing care documentation was 68.59 (5.13). Conclusion: Nurses perceived behaviors control over nursing care documentation were slighty over the mediocre values, Nurses tend to have positive perception on their control over documenting nursing care.